Cochrane Database of Systematic Reviews 2005
DOI: 10.1002/14651858.cd003715.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Oral 5-aminosalicylic acid for maintenance of medically-induced remission in Crohn's disease

Abstract: We found no evidence in this review to suggest that 5-ASA preparations are superior to placebo for the maintenance of medically-induced remission in patients with Crohn's disease. Therefore it appears that additional randomised trials of this regime are not justified.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
98
3
7

Year Published

2006
2006
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 123 publications
(110 citation statements)
references
References 31 publications
2
98
3
7
Order By: Relevance
“…Their efficacy in the treatment of Crohn's disease has become somewhat more controversial [110,[351][352][353][354]. These agents have a long history of clinical use and have been extensively studied in clinical trials for both ulcerative colitis [355,356] and Crohn's disease [357,358]. Sulfasalazine, the prototype aminosalicylate formulation, was developed with the concept of providing both an antibacterial (sulfapyridine) and antiinflammatory (5-aminosalicylic acid, mesalamine, mesalazine) agent into the connective tissues [359].…”
Section: Aminosalicylatesmentioning
confidence: 99%
See 1 more Smart Citation
“…Their efficacy in the treatment of Crohn's disease has become somewhat more controversial [110,[351][352][353][354]. These agents have a long history of clinical use and have been extensively studied in clinical trials for both ulcerative colitis [355,356] and Crohn's disease [357,358]. Sulfasalazine, the prototype aminosalicylate formulation, was developed with the concept of providing both an antibacterial (sulfapyridine) and antiinflammatory (5-aminosalicylic acid, mesalamine, mesalazine) agent into the connective tissues [359].…”
Section: Aminosalicylatesmentioning
confidence: 99%
“…Although sulfasalazine has been commonly used to prevent relapse for patients with quiescent Crohn's disease, neither the National Cooperative Crohn's Disease Study nor the European Cooperative Crohn's Disease Study demonstrated maintenance benefits at (low) dosages of 1-3 g/day. While one trial utilizing a 3 g/day dosage of sulfasalazine demonstrated efficacy at reducing the likelihood of postoperative clinical recurrence [409] there remains little evidence of a maintenance benefit after medically-induced clinical remissions [358].…”
Section: Aminosalicylates In Crohn's Disease Mild To Moderate Active mentioning
confidence: 99%
“…As obvious from Cochrane reviews and meta-analyses, the benefit of sulfasalazine and 5-aminosalicylic acid (5-ASA) preparations in uncomplicated CD is quite limited [2,3,4]. In a meta-analysis of three double-blind randomized studies on the role of 5-ASA in the treatment of active CD, 4 g/day 5-ASA was superior to placebo in reducing the Crohn's disease activity index (CDAI); however, the clinical effect was not convincing [4,5].…”
Section: What Does ‘Step Up' Mean For Crohn's Disease Therapy?mentioning
confidence: 99%
“…There is a growing body of evidence that shows that 5-aminosalicylic acid derivatives are not effective in CD with the exception of sulfasalazine in colonic CD [11,12], however they are still frequently used as part of “step-up” care. In this treatment approach, corticosteroids are considered the cornerstone of induction therapy for patients with severely active CD.…”
Section: Introductionmentioning
confidence: 99%